Perception on veneers in relation to Islamic perspective in Kuantan community - Ahmad Muzamir, Liyana Shafiqah; Mohamad Kamil, Husna; Muhamad Halil, Mohd Haikal; Yacob, Norlela (IIUM Press, 2026)
In aesthetic dentistry, veneer has widely performed cosmetic treatments in dentistry. It has gained increasing popularity due to rising social and psychological demands for improved dental appearance to get the ‘idealized smile’ or ‘Hollywood smile’. This has raised ethical concern on dental treatment of overtreatment. Within Muslim communities, however, these procedures raise important concerns from the perspective of Islamic jurisprudence (fiqh). This study aimed to assess the Kuantan community’s knowledge, perceptions, and understanding of veneer treatment within both dental and religious contexts based on clinical photographic given. A cross-sectional online survey was conducted through online platforms. A total of 250 respondents with mean age was 32.8 years (SD = 12.18), with 30% male and 70% female participants. Findings showed that overall knowledge of aesthetic dentistry and veneers was at a moderate level (52%). While 78.8% of respondents agreed that treatment decisions should be guided by intention (niyyah), only 24% correctly identified the hukm of veneers, and 43% remained unsure. No significant associations were found between knowledge and demographic or social variables. Although a significant difference was observed between knowledge and perception, their correlation was weak, suggesting that awareness does not necessarily translate into accurate understanding. These findings highlight limited comprehension of Islamic legal maxims concerning aesthetic dental procedures. While veneers may be permissible when addressing medical or psychological needs, their use solely for beautification remains prohibited. Therefore, a recommendation to broader the educational initiatives needed to enhance understanding of both the clinical and religious aspects of cosmetic dentistry.